Mechanistic and functional diversity in the mechanosensory kinases of the titin-like family. (18th July 2013) - Mayans, Olga; Benian, Guy M.; Simkovic, Felix; Rigden, Daniel J.
Abstract : The giant cytoskeletal kinases of the titin-like family are emerging as key mediators of stretch-sensing in muscle. It is thought that their elastic conformational deformation during muscle function regulates both their catalysis and the recruitment of regulatory proteins to signalosomes that assemble in their vicinity. In the present article, we discuss the speciation of mechanosensory mechanisms in titin-like kinases, their scaffolding properties and the kinase/pseudokinase domain variations that define a rich functional diversity across the family.